EFFECTS OF 1-METHYLCYCLOPROPENE (1-MCP) COUPLED WITH CONTROLLED ATMOSPHERE STORAGE ON THE RIPENING AND QUALITY OF ‘CAVENDISH’ BANANA - Liana Suryaningsih1; James P. Mattheis2 (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2017)
ABSTRACT Fresh-fruit banana is well known to have a short-life after harvest. A short pre-pilot study was carried out to test the effect of atmospheric condition exposure to 1-MCP on the quality, limited to CO2 production, cosmetic and flesh appearance, and shelf life of fresh-fruit bananas. Low level of O2 (3 kPa) and high level of CO2 (6 kPa) and 1-MCP (350 ppb for 18 hours), alone or in combination did prevent the browning on the fruit skin after 11 days in Controlled Atmosphere (CA) storage. However, these treatments did not prevent browning on the fruit skin once upon removal from the storage. The appearance of the flesh for all treatments was relatively the same for both in the CA storage and after storage. Fruits treated with 1-MCP and CA storage showed the highest level of CO2 production followed by fruits treated with CA storage only and untreated fruits respectively.